2015
DOI: 10.1111/asj.12386
|View full text |Cite
|
Sign up to set email alerts
|

Early post mortem expression of genes related to tenderization in two Italian Simmental young bulls' skeletal muscles differing in contractile type

Abstract: The early post mortem expression of eight genes potentially involved in meat ageing process and the tenderness of two Italian Simmental young bulls' (Bos taurus) skeletal muscles differing in their contractile type were evaluated. Samples of Longissimus lumborum (LL) and Infraspinatus (IS) muscles were collected from 17 bulls. The messenger RNA (mRNA) abundances of calpain-1, calpain-2, calpastatin, caspase 3, caspase 9, heat shock protein 27 (Hsp27), Hsp40 and Hsp70 were detected by quantitative PCR. The myos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 52 publications
1
22
1
3
Order By: Relevance
“…Calpastatin gene expression has an average of nearly 30% in high WBSF groups compared with low WBSF at 6 days postmortem (42). Moreover, calpain-1 mRNA abundance was slightly higher and calpastatin mRNA was lower in longissimus lumborum than infraspinatus (41), suggesting that the higher proportion of glycolytic fibers could improve the tenderness of certain muscles by accelerating post mortem aging due to the presence of a higher calpain/calpastatin ratio (43). Other researcher reveal that the slightly lower tenderness of meat from Zebu animals is probably not a result of lower expression of genes encoding proteases, but rather is due to the increased expression of CAST (44).…”
Section: El Nuevo Marcador Capn1 4751 Fue úTil En Poblaciones De Bovimentioning
confidence: 94%
See 2 more Smart Citations
“…Calpastatin gene expression has an average of nearly 30% in high WBSF groups compared with low WBSF at 6 days postmortem (42). Moreover, calpain-1 mRNA abundance was slightly higher and calpastatin mRNA was lower in longissimus lumborum than infraspinatus (41), suggesting that the higher proportion of glycolytic fibers could improve the tenderness of certain muscles by accelerating post mortem aging due to the presence of a higher calpain/calpastatin ratio (43). Other researcher reveal that the slightly lower tenderness of meat from Zebu animals is probably not a result of lower expression of genes encoding proteases, but rather is due to the increased expression of CAST (44).…”
Section: El Nuevo Marcador Capn1 4751 Fue úTil En Poblaciones De Bovimentioning
confidence: 94%
“…Algunos autores sugieren que el tipo de músculo y/o el tipo de fibra pueden influir en la expresión y/o actividades de la calpaína y la calpastatina y por lo tanto podrían explicar la proteólisis post mortem y la tenderización de la carne (39)(40)(41). Se encontraron diferencias en la subunidad pequeña (CAPNS1) y variantes en la expresión de CAST en los músculos con fibras de tipo lento en comparación con los músculos con fibras de tipo rápido (40).…”
Section: El Nuevo Marcador Capn1 4751 Fue úTil En Poblaciones De Boviunclassified
See 1 more Smart Citation
“…Becila et al (2010) provided evidences that cell death in post-mortem muscle occurs via an apoptotic process, in which caspase 3 and caspase 9 operate. Although caspases are the main effectors of apoptosis, their importance in meat tenderisation process is still debated (Sacc a et al 2015a). For their physiological role as chaperones, anti-apoptotic and anti-oxidative factors, heat shock proteins are involved in the transformation of muscle to meat (Cassar-Malek and Picard 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For their physiological role as chaperones, anti-apoptotic and anti-oxidative factors, heat shock proteins are involved in the transformation of muscle to meat (Cassar-Malek and Picard 2016). Among these, alphaB-cristallyn and heat shock protein 27 (Hsp27) have been shown to be involved in myofibrillar proteins protection (Guillemin et al 2011;Lomiwes et al 2014) and Hsp27 was reported as related to tenderness (Bernard et al 2007;Sacc a et al 2015a). Besides having a significant role in cell thermotolerance, Hsp70 has been shown to inhibit the apoptotic pathways and appears to be a good biomarker of low tenderness (Kregel 2002;Picard et al 2014).…”
Section: Introductionmentioning
confidence: 99%